2014
DOI: 10.7314/apjcp.2014.15.18.7707
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Poster Presentations on Academic Knowledge Transfer from the Oncologist Perspective in Turkey

Abstract: Background: Currently poster presentations offer a common visual medium for knowledge transfer by a wide range of health professionals. Our study aimed to determine the scientific importance of poster presentations for Medical and Radiation Oncologists. Methods: A survey form including 40 questions was distributed to a total of 131 oncologists experienced in poster presentations. One hundred completed survey forms were included in the study. Descriptive statistics and modified thematic analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Most Biology Education students believe that posters are effective for conveying information and for the occurrence of academic debate. This is in line with Arslan et al [19] research that 131 or 64% of respondents agree that posters are a good medium for knowledge transfer.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most Biology Education students believe that posters are effective for conveying information and for the occurrence of academic debate. This is in line with Arslan et al [19] research that 131 or 64% of respondents agree that posters are a good medium for knowledge transfer.…”
Section: Discussionsupporting
confidence: 91%
“…From the aesthetic aspect, the poster highlights visual appeal more than text. According to Arslan et al [19], 70% of 131 respondents agreed that the appearance of a poster can help attract more viewers' attention. Furthermore, graphic design and physical appearance can determine success in promoting knowledge transfer [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While contributed posters are often intended to be as prestigious as contributed talks at scientific meetings, that is not the general interpretation. One survey found that only 64% of participants thought that posters were a good medium for knowledge transfer . In another study of national and international meetings, very few (<5%) of the meeting participants visited posters, few read them, and even fewer asked useful questions .…”
mentioning
confidence: 99%
“…One survey found that only 64% of participants thought that posters were a good medium for knowledge transfer. 2 In another study of national and international meetings, very few (< 5%) of the meeting participants visited posters, few read them, and even fewer asked useful questions. 3 Th e subsequent recall of poster material was abysmal.…”
mentioning
confidence: 99%